1980
DOI: 10.21273/jashs.105.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Strawberry Meristems and Mass Propagation of Plantlets1

Abstract: Meristems isolated from strawberry (Fragaria X ananassa Duch. cv. Redcoat) runner-tips were cultured on a Murashige and Skoog (MS) medium supplemented with 6-benzylamino purine (BA), indolebutyric acid (IBA) and gibberellic acid (GA3) at concentrations of 1, 1 and 0.1 μm, respectively. The meristems regenerated shoots within 3 to 4 weeks when incubated at 26°, 16 hour photoperiods and 4000 lux intensity. On medium supplemented with BA at a concentration of 10 μm these shoots proliferated into “clumps,” each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Apical meristems of strawberry crowns ('Kent' and 'Honey oye') were excised according to Boxus (2). After an initiation period on Boxus medium (2), the plantlets were transferred to a proliferation medium (16) and subcultured five to six times at regular 4-week intervals. Axillary branches located at the base of cultures then were excised and transferred onto rooting medium.…”
Section: Methodsmentioning
confidence: 99%
“…Apical meristems of strawberry crowns ('Kent' and 'Honey oye') were excised according to Boxus (2). After an initiation period on Boxus medium (2), the plantlets were transferred to a proliferation medium (16) and subcultured five to six times at regular 4-week intervals. Axillary branches located at the base of cultures then were excised and transferred onto rooting medium.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors indicated that cold hardening and /or preculturing with a high concentrations of sugar in the medium are essential to successful cryopreservation of In vitro cultured plant materials (Kartha et al, 1979(Kartha et al, , 1980Engelmann et al, 1995;Reed 1988Reed , 1990Reed , 1992Dereddure et al, 1990;Niino, et al, 1992;Kartha and Engelmann 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue culture studies in strawberry primarily have been confined to meristem culture for virus elimination, vegetative propagation, and cryopreservation of germplasm (Boxus et al, 1977;Kartha et al, 1980). However, it recently has been demonstrated that plant regeneration is also possible from both primary and subcultured callus induced on immature leaves (Nehra et al, 1988;Jones et al, 1988).…”
mentioning
confidence: 99%